Catalysis of Michael additions by covalently modified G-quadruplex DNA - Dey, Surjendu; Rühl, Carmen L.; Jäschke, Andres (Chemistry - a European journal, 2017)
Enantioselective catalysis utilizing G-quadruplex DNA-based artificial metalloenzymes has emerged as a new approach in the field of aqueous-phase homogeneous catalysis. Recently, a catalytic asymmetric Michael addition employing a covalently modified G-quadruplex in combination with CuII ions has been reported. Here we assess, by systematic chemical variation and using various spectrometric techniques, a variety of parameters that govern rate acceleration and stereoselectivity of the reaction, such as the position of modification, the topology of the quadruplex, the nature of the ligand, the length of the linker between ligand and DNA, the chemical identity of monovalent ions and transition metal complexes. The DNA quadruplex modified at position 10 (dU10) with hexynyl-linked bpy ligand showed twice the initial reaction rate as compared with the DNA strand derivatized at position 12 (dU12). The strikingly different dependence of the stereoselectivity on the linker length, and their different spectroscopic properties indicate large differences in the architecture of the catalytic centers between the dU10-derivatized and the dU12-modified quadruplexes. Upon addition of CuII, both types of bpy-derivatized DNA strands form defined 1:1 Cu-DNA complexes stable enough for mass spectrometric analysis, while the underivatized strands exhibit weak and unspecific binding, correlated with much lower catalytic rate acceleration. Both dU10- and dU12-derivatized quadruplexes could be reused ten times without reduction of stereoselectivity.